Perspektif Filsafat Progresivisme terkait Siswa Slow Learner dalam Pembelajaran - Gea, Masniari; Simanjuntak, Maharani; Lende, Adrianus; Batee, Herlin Rostati (IAKN Ambon, 2023)
This research employs a qualitative method with a literature review approach to explore the positive impact of the progressive philosophy approach on the learning outcomes and development of slow learner students. In the context of slow learner students with IQ scores ranging from 70 to 90, traditional learning environments often pose challenges. By adopting the principles of progressivism as advocated by John Dewey, this study aims to enhance the engagement and understanding of slow learner students through direct experiences, active participation, and problem-solving. The findings of the research conclude that the progressive approach provides an effective learning method for slow learner students. Principles such as direct experience, active participation, and problem-solving contribute to increased engagement and understanding in the learning process. The research highlights that implementing teaching strategies aligned with progressive principles can assist slow learner students in overcoming learning barriers and achieving positive development within the context of inclusive education. Recommendations from this study underscore the need for developing an inclusive curriculum for slow learner students using the progressive approach. Collaboration between teachers and curriculum developers is considered crucial to creating learning materials accessible to all students, including those with special needs. This research serves as a foundation for further development in creating a learning environment supportive of the growth and development of slow learner students within the inclusive education system.